IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PENDIDIKAN (SIMP) DENGAN MENGGUNAKAN APLIKASI AFRESTO DI SMK NEGERI 5 PENAJAM PASER UTARA - ediansyah; agus dedi; Ramadiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the implementation of an Educational Management Information System (EMIS) using the Afresto platform at SMK Negeri 5 Penajam Paser Utara to enhance the quality of educational management. The research is motivated by the school’s need to integrate digital technology into academic, administrative, and service management processes, in line with the demands of the Industrial 4.0 era. A qualitative descriptive method was applied, with data collected through observations, interviews, and document analysis. The findings indicate that Afresto is effective in managing academic data, streamlining administrative workflows, facilitating information access, and improving reporting accuracy. The main challenges include varying levels of digital literacy among users and limited network infrastructure. In conclusion, Afresto has the potential to serve as an efficient EMIS model, provided it is supported by ongoing training and adequate infrastructure.